2017
DOI: 10.3389/fnins.2017.00678
|View full text |Cite
|
Sign up to set email alerts
|

Sequestosome 1 Deficiency Delays, but Does Not Prevent Brain Damage Formation Following Acute Brain Injury in Adult Mice

Abstract: Neuronal degeneration following traumatic brain injury (TBI) leads to intracellular accumulation of dysfunctional proteins and organelles. Autophagy may serve to facilitate degradation to overcome protein debris load and therefore be an important pro-survival factor. On the contrary, clearing may serve as pro-death factor by removal of essential or required proteins involved in pro-survival cascades. Sequestosome 1 (SQSTM1/p62) is a main regulator of the autophagic pathway that directs ubiquinated cargoes to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…It is one of the first markers of autophagy studied in the context of TBI and is probably the better known. The increment of the protein starts in the first four hours after the trauma, although the rise is not always significant [8,15]. However, all the studies agree in demonstrating a long elevation of the protein that was found to arise also at 15 days [9] or 32 days [10].…”
Section: Lipidated Microtubule-associated Protein Light-chain 3 (Lc3-ii)mentioning
confidence: 66%
“…It is one of the first markers of autophagy studied in the context of TBI and is probably the better known. The increment of the protein starts in the first four hours after the trauma, although the rise is not always significant [8,15]. However, all the studies agree in demonstrating a long elevation of the protein that was found to arise also at 15 days [9] or 32 days [10].…”
Section: Lipidated Microtubule-associated Protein Light-chain 3 (Lc3-ii)mentioning
confidence: 66%
“…Our results indicated that autophagy markers (Apg5l, Lc3b and Sqstm1) did not show any changes in their expression at the six-month post-TBI time point, though after 12 months the 11.5 Gy, BBT-059 group showed a significant decrease in Sqstm1 expression compared to all other groups. Sqstm1 is the main regulator of the autophagic pathway that directs ubiquitinated cargoes to autophagosomes for degradation (Sebastiani et al, 2017). Autophagy is an evolutionarily conserved process, morphologically it is involved in the formation of double-membrane bound vesicles known as autophagosomes or autophagic vacuoles that degrade, thus recycling proteins and cellular organelles by fusion with lysosomes (Yang and Klionsky, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Motor coordination was analyzed by the rotarod test as described previously and by an investigator blinded to the group allocation [ 17 ]. After 3 days after TBI, mice were tested twice (two rounds of testing task) before euthanasia.…”
Section: Methodsmentioning
confidence: 99%